LEARNING BEYOND BORDERS: MALAYSIAN STUDENTS’ INSIGHTS FROM HYU ERICA, KOREA - Mahzaton Aqma, Abu Talip (UMPSA, 2025)
PEKAN, 6 September 2025 - On Saturday from 10:00 a.m. to 12:00 p.m., the Korean Language Unit of the Centre for Modern Languages (CML) hosted a Basic Global Classroom via Google Meet with two Malaysian students, Hessa Sarah Binti Mohd Roslan and Ain Ardini Haifa Binti Sahabudin, who are currently pursuing their studies at Hanyang University (HYU) ERICA Campus in South Korea. This session formed part of ongoing efforts to prepare Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Korean Dual Degree Programme students for their academic journey abroad through direct peer-to-peer sharing and collaborative learning